Improving Students’ Mathematical Understanding and Problem-Solving Performance through the Integration of Quantum Learning and Interactive Digital Assessment - Anelia Kusuma Ningrum; Netriwati Netriwati; Siska Andriani (CV. SPDFHarmony, 2025)
Background: Difficulties in developing mathematical conceptual understanding and problem-solving ability persist in secondary education, indicating the need for learning approaches that actively engage students and make use of digital assessment support. Aims: This study sought to investigate how the integration of Quantum Learning with interactive digital assessment influences students’ mathematical conceptual understanding and problem-solving performance, both as separate outcomes and in combination. Methods: The study adopted a quantitative quasi-experimental design involving 190 tenth-grade students selected through cluster random sampling. Two experimental groups and one control group were formed. Quantum Learning was applied in the experimental classes, with one group receiving additional support through interactive digital assessment, while the control class followed conventional instruction. Data were obtained through validated essay tests and analyzed using MANOVA after the assumptions of normality and homogeneity were fulfilled. Result: The analysis revealed meaningful differences in both conceptual understanding and problem-solving performance between students in the experimental and control groups. Learners exposed to Quantum Learning supported by interactive digital assessment demonstrated higher achievement levels than those taught using conventional methods. Multivariate testing confirmed a statistically significant simultaneous effect of the instructional model on both learning outcomes. Conclusion: Integrating Quantum Learning with interactive digital assessment contributes to stronger mathematical understanding and more effective problem-solving performance. This approach supports active participation and meaningful learning processes, suggesting its potential value for contemporary mathematics instruction.